2010
DOI: 10.1038/hr.2010.9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of obesity-induced hypertension

Abstract: The relationship between obesity and hypertension is well established both in children and adults. The mechanisms through which obesity directly causes hypertension are still an area of research. Activation of the sympathetic nervous system has been considered to have an important function in the pathogenesis of obesity-related hypertension. The arterial-pressure control mechanism of diuresis and natriuresis, according to the principle of infinite feedback gain, seems to be shifted toward higher blood-pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
390
0
64

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 534 publications
(491 citation statements)
references
References 92 publications
20
390
0
64
Order By: Relevance
“…Insulin resistance increases the endothelial expression of PAI-1 and cellular adhesion molecules, 33,34 suggesting that multiple mechanisms may contribute to accelerated atherosclerosis. 7,35 Thus, the decrease in PAI-1 concentration observed in this investigation may help to attenuate the monocyte migratory capacity mediated by insulin in a pro-inflammatory and atherothrombotic state. This mechanism should be investigated more fully.…”
Section: Discussionmentioning
confidence: 74%
“…Insulin resistance increases the endothelial expression of PAI-1 and cellular adhesion molecules, 33,34 suggesting that multiple mechanisms may contribute to accelerated atherosclerosis. 7,35 Thus, the decrease in PAI-1 concentration observed in this investigation may help to attenuate the monocyte migratory capacity mediated by insulin in a pro-inflammatory and atherothrombotic state. This mechanism should be investigated more fully.…”
Section: Discussionmentioning
confidence: 74%
“…BMI is determined by cheap anthropometric measurements, which can be carried out annually in schools and can be used as a simple screening tool, inserted into comprehensive public health strategies, focused on preventive actions. 23 Another interesting finding is that, although obesity presents a great burden in the hypertension genesis, 17 all analyzed cutoffs presented poor screening characteristics, indicating that without adequate cutoffs, %BF monitoring may not allow for complete hypertension screening.…”
Section: Discussionmentioning
confidence: 95%
“…This decreased effect of nitric oxide is associated with endothelial dysfunction and, thus, arterial hypertension. 17 In pediatric populations, previous studies have found that high SBP is frequently related to higher adiposity, 3,16 indicating that the above-mentioned mechanisms could occur not only in adults, but also in children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…1 This increase represents a problem for the healthcare system, as being overweight is directly associated with an increased probability of developing metabolic syndrome and high blood pressure. 2,3 The screening performed by Fernandes et al 4 used body mass index (BMI) and dual-energy X-ray absorptiometry (DXA), which is a more accurate method for assessing body composition, as DXA assesses three aspects of body composition: bone mineral, lipids (triglycerides, phospholipid membranes and so on) and lipid-free soft tissue. From these data, we can estimate fat mass, lean soft tissue mass, fat-free mass, soft tissue mass, total body mass and percent fat mass.…”
mentioning
confidence: 99%